Tau hadronic branching ratios - BUSKULIC, D. (Institutional Knowledge at Singapore Management University, 1996)
From 64492 selected τ-pair events, produced at the Z0 resonance, the measurement of the tau decays into hadrons from a global analysis using 1991, 1992 and 1993 ALEPH data is presented. Special emphasis is given to the reconstruction of photons and π0s, and the removal of fake photons. A detailed study of the systematics entering the π0 reconstruction is also given. A complete and consistent set of tau hadronic branching ratios is presented for 18 exclusive modes. Most measurements are more precise than the present world average. The new level of precision reached allows a stringent test τ-μ, universality in hadronic decays, ${cal G}_{∢u}/{cal G}_{ώ}=1.0013pm 0.0095$, and the first measurement of the vector and axial-vector contributions to the non-strange hadronic τ decay width: Rτ,V = 1.788 ± 0 0.025 and Rτ,A = 1.694 ± 0.027. The ratio (Rτ,V − Rτ,A)/(Rτ,V + Rτ,A), equal to (2.7 ± 1.3) %, is a measure of the importance of QCD non-perturbative contributions to the hadronic τ decay width.